A CORRELATION STUDY ON STUDENTS’ ABILITY IN LITERAL READING AND PARAGRAPH WRITING - Findy Mia Ameilia; Daning Hentasmaka; Rosi Anjarwati; Ima Chusnul Chotimah (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
This research investigated the correlation between adult EFL students’ literal reading and paragraph writing. Since adult EFL learners in tertiary education learn about literal reading and paragraph writing in more detail, a more specific investigation on the literal and paragraph writing of adult EFL students has not been conducted. The researcher uses a quantitative approach with a correlational design. This research followed by twenty-nine respondents from the second semester student in the English Department of STKIP PGRI Jombang. The participant was taken by using a purposive sampling technique. In the data were taken by using reading and writing tests which were developed by the lecturers. The data collected were then analysed by using non-parametric Spearman’s rho with the help of SPSS version 22. The results of the data analysis showed the value of Sig (2-tailed) .037. and the value of correlational coefficient was .388. Those values indicated a significant positive yet low correlation between adult EFL students’ literal reading and paragraph writing.